Prognostic significance of minimal residual disease in high risk B-ALL: a report from Children's Oncology Group study AALL0232 - Borowitz, Michael J; Wood, Brent L; Devidas, Meenakshi; Loh, Mignon L; Raetz, Elizabeth A; Salzer, Wanda L; Nachman, James B; Carroll, Andrew J; Heerema, Nyla A; Gastier-Foster, Julie M; Willman, Cheryl L; Dai, Yunfeng; et al. (Blood, 2015)
Minimal residual disease (MRD) is highly prognostic in pediatric B-precursor acute lymphoblastic leukemia (B-ALL). In Children's Oncology Group high-risk B-ALL study AALL0232, we investigated MRD in subjects randomized in a 2 × 2 factorial design to receive either high-dose methotrexate (HD-MTX) or Capizzi methotrexate (C-MTX) during interim maintenance (IM) or prednisone or dexamethasone during induction. Subjects with end-induction MRD ≥0.1% or those with morphologic slow early response were nonrandomly assigned to receive a second IM and delayed intensification phase. MRD was measured by 6-color flow cytometry in 1 of 2 reference labs, with excellent agreement between the two. Subjects with end-induction MRD <0.01% had a 5-year event-free survival (EFS) of 87% ± 1% vs 74% ± 4% for those with MRD 0.01% to 0.1%; increasing MRD amounts was associated with progressively worse outcome. Subjects converting from MRD positive to negative by end consolidation had a relatively favorable 79% ± 5% 5-year disease-free survival vs 39% ± 7% for those with MRD ≥0.01%. Although HD-MTX was superior to C-MTX, MRD retained prognostic significance in both groups (86% ± 2% vs 58% ± 4% for MRD-negative vs positive C-MTX subjects; 88% ± 2% vs 68% ± 4% for HD-MTX subjects). Intensified therapy given to subjects with MRD >0.1% did not improve either 5-year EFS or overall survival (OS). However, these subjects showed an early relapse rate similar to that seen in MRD-negative ones, with EFS/OS curves for patients with 0.1% to 1% MRD crossing those with 0.01% to 0.1% MRD at 3 and 4 years, thus suggesting that the intensified therapy altered the disease course of MRD-positive subjects. Additional interventions targeted at the MRD-positive group may further improve outcome. This trial was registered at www.clinicaltrials.gov as #NCT00075725.